Realization of DC electronic loads for energy storage testing - Ong, Teng Ho. (2011)
Almost all modern electronic and electrical devices are built in with power supply. The increasing researches on energy storage systems brings along the need for better and more efficient test equipments. A DC electronic load is one such system that is capable of testing all sorts DC output power supplies.